The Association Between Students’ Digital Literacy and Adaptation to EdLink-Based Learning: A Single-University Correlational Study - Abdillah SAS; Supriadi Syam; Sahabuddin Rifai; Muh Fadli Fauzi Sahlan (Jurusan Teknik Informatika dan Komputer, 2026)
Purpose - This study aims to examine the association between students’ digital literacy and their adaptation to EdLink-based learning in higher education. Design/methods/approach - A quantitative cross-sectional correlational design was employed. Data were collected from 290 undergraduate students at Universitas Bosowa who had used EdLink for learning activities. The instrument consisted of two self-reported scales measuring digital literacy and adaptation to EdLink-based learning. Data were analyzed using descriptive statistics, validity and reliability testing, assumption testing, Pearson correlation, and simple linear regression. Findings - The results showed a positive and statistically significant association between digital literacy and students’ adaptation to EdLink-based learning (r = 0.892; R² = 0.795; p < 0.001). Students with higher digital literacy tended to report higher adaptation to EdLink-based learning. However, this finding should be interpreted as correlational rather than causal evidence because the study did not test mediation, moderation, or institutional factors. The very strong association may also reflect self-reported measurement, conceptual proximity between the constructs, and possible common method variance. Research limitations/implications - This study was limited to one university and relied on self-reported questionnaire data. Other factors, such as learning motivation, lecturer support, platform usability, digital infrastructure, and prior LMS experience, were not examined. Originality/value - This study provides contextual evidence from an Indonesian university on the association between students’ digital literacy and adaptation to EdLink-based learning.